Der Einfluss des Lösungsmittels auf die Kristallwachstumskinetik - J.R. Bourne (CHIMIA)
This review is based upon the results of recent research, which has clarified the role played by the solvent in determining the mechanism and the kinetics of crystal growth from solution. The strength of the interaction between solid and solution (ΦLS) is among the parameters which determine the degree of roughness and irregularity at the molecular scale of the crystal surface. A rough, diffuse interface exhibits linear kinetics, while a smooth surface grows with second order or other forms of non-linear kinetics. The growth kinetics of organic crystals from different solvents have been interpreted by means of variations in ΦLS, which influence the surface roughness and hence the kinetics. The solvent giving the greater solubility of a given solid is associated with the faster inherent growth kinetics in the few cases which have so far been studied.